Robocasting of advanced ceramics: ink optimization and protocol to predict the printing parameters - A review - Soukaina Lamnini; Hamada Elsayed; Yazid Lakhdar; Francesco Baino; Federico Smeacetto; Enrico Bernardo (Heliyon, 2022)
Direct-Ink-Writing (or robocasting) is a subset of extrusion-based additive manufacturing techniques that has grown significantly in recent years to design simple to complex ceramic structures. Robocasting, relies on the use of high-concentration powder pastes, also known as inks. A successful optimization of ink rheology and formulation constitutes the major key factor to ensure printability for the fabrication of self-supporting ceramic structures with a very precise dimensional resolution. However, to date achieving a real balance between a comprehensive optimization of ink rheology and the determination of a relevant protocol to predict the printing parameters for a given ink is still relatively scarce and has been not yet standardized in the literature.The current review reports, in its first part, a detailed survey of recent studies on how ink constituents and composition affect the direct-ink-writing of ceramic parts, taking into account innovative ceramic-based-inks formulations and processing techniques. Precisely, the review elaborates the major factors influencing on ink rheology and printability, specifically binder type, particle physical features (size, morphology and density) and ceramic feedstock content.In the second part, this review suggests a standardized guideline to effectively adapt a suitable setting of the printing parameters, such as printing speed and pressure, printing substrate, strut spacing, layer height, nozzle diameter in function of ink intrinsic rheology.